Social determinants of leprosy in a hyperendemic State in North Brazil - Lorena Dias Monteiro; Rosa Maria Salani Mota; Francisco Rogerlândio Martins-Melo; Carlos Henrique Alencar; Jorg Heukelbach
ABSTRACT OBJECTIVE To identify the socioeconomic, demographic, operational, and health service-related factors associated with the occurrence of leprosy in a hyperendemic State in North Brazil. METHODS This is an ecological study based on secondary data from the Sistema de Informações de Agravos de Notificação in municipalities of the State of Tocantins from 2001 to 2012. Units of analysis were the 139 municipalities of the State. Negative binomial log linear regression models were used to estimate incidence rate ratios. RESULTS In bivariate analysis, the incidence rate ratios were significantly higher for municipalities with higher income ratio of the poorest 20.0% (1.47; 95%CI 1.19-1.81) and better Municipal Human Development Index (1.53; 95%CI 1.14-2.06). In multivariate analysis, the incidence rate ratios were significantly higher in municipalities with higher proportion of immigrants (1.31; 95%CI 1.11-1.55) and higher proportion of households with waste collection (1.37; 95%CI 1.11-1.69). There was a significant reduction in the incidence rate ratio with increased coverage of the Bolsa Família Program (0.98; 95%CI 0.96-0.99). CONCLUSIONS Control programs need to focus on activities in municipalities of greater social vulnerability with intersectoral investment for the improvement of the living conditions of the population.